2014
DOI: 10.5539/ass.v10n6p161
|View full text |Cite
|
Sign up to set email alerts
|

Do the Big 4 and the Second-Tier Firms Provide Audits of Similar Independence?

Abstract: In this paper, we examine the relation between the Big 4 and Second-tier auditors with auditor independence. Prior research suggests that the Big 4 audit firms are of higher independence than are non-Big 4 firms. The study also indicates a view that, both the public company respondents and audit firm respondents perceived the Big Four audit firms as having a higher auditor independence than other audit firms, which is consistent with findings of (Abu Bakar et al., 2005;DeAngelo, 1981b) Data were collected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The findings revealed that the majority of the prior empirical studies (75 studies) were quantitative research. Whereas six studies were qualitative (Al-Twaijry 1 et al, 2002; Abuazza et al, 2015; Elbardan & Ali, 2012; Khelil, Hussainey, & Noubbigh, 2018; Khelil, Akrout et al, 2018; Khelil & Khlif, 2022; Sawan & Hamuda, 2014), one review research (Alahmadi et al, 2017), three non-empirical studies (Elbardan & Ali, 2011; Ngoc Huy, 2013), one descriptive study (Hussain & Mallin, 2002), and five mix method studies (Al-Twaijry et al, 2003; Al-Sukker et al, 2018; El-Sayed Ebaid, 2011; Khelil et al, 2016). From these articles, four studies investigate the mediating effect of various factors such as job burnout (Shbail et al, 2018), IA quality (Bshayreh et al, 2019; Mustafa & Al-Nimer, 2018), job satisfaction (Obeid et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed that the majority of the prior empirical studies (75 studies) were quantitative research. Whereas six studies were qualitative (Al-Twaijry 1 et al, 2002; Abuazza et al, 2015; Elbardan & Ali, 2012; Khelil, Hussainey, & Noubbigh, 2018; Khelil, Akrout et al, 2018; Khelil & Khlif, 2022; Sawan & Hamuda, 2014), one review research (Alahmadi et al, 2017), three non-empirical studies (Elbardan & Ali, 2011; Ngoc Huy, 2013), one descriptive study (Hussain & Mallin, 2002), and five mix method studies (Al-Twaijry et al, 2003; Al-Sukker et al, 2018; El-Sayed Ebaid, 2011; Khelil et al, 2016). From these articles, four studies investigate the mediating effect of various factors such as job burnout (Shbail et al, 2018), IA quality (Bshayreh et al, 2019; Mustafa & Al-Nimer, 2018), job satisfaction (Obeid et al, 2017).…”
Section: Resultsmentioning
confidence: 99%